Comparison of Ginsenoside Components of Various Tissues of New Zealand Forest-Grown Asian Ginseng (Panax Ginseng) and American Ginseng (Panax Quinquefolium L.) - Chen, Wei (Biomolecules, 2020)
Asian ginseng (Panax ginseng) and American ginseng (Panax quinquefolium L.) are the two most important ginseng species for their medicinal properties. Ginseng is not only popular to consume, but is also increasingly popular to cultivate. In the North Island of New Zealand, Asian ginseng and American ginseng have been grown in Taupo and Rotorua for more than 15 years. There are no publications comparing the chemical constituents between New Zealand-grown Asian ginseng (NZPG) and New Zealand-grown American ginseng (NZPQ). In this study, fourteen ginsenoside reference standards and LC–MS(2) technology were employed to analyze the ginsenoside components of various parts (fine root, rhizome, main root, stem, and leaf) from NZPG and NZPQ. Fifty and 43 ginsenosides were identified from various parts of NZPG and NZPQ, respectively, and 29 ginsenosides were found in both ginseng species. Ginsenoside concentrations in different parts of ginsengs were varied. Compared to other tissues, the fine roots contained the most abundant ginsenosides, not only in NZPG (142.49 ± 1.14 mg/g) but also in NZPQ (115.69 ± 3.51 mg/g). For the individual ginsenosides of both NZPG and NZPQ, concentration of Rb1 was highest in the underground parts (fine root, rhizome, and main root), and ginsenoside Re was highest in the aboveground parts (stem and leaf).